Monitoring the Impact of Floods on Water Quality Using Optical Remote Sensing Imagery: The Case of Lake Karla (Greece) (2024)
Perivolioti, T.-M.; Zachopoulos, K.; Zioga, M.; Tompoulidou, M.; Katsavouni, S.; Kemitzoglou, D.; Terzopoulos, D.; Mouratidis, A.; Tsiaoussi, V. Monitoring the Impact of Floods on Water Quality Using Optical Remote Sensing Imagery: The Case of Lake Karla (Greece). Water 2024, 16, 3502. https://doi.org/10.3390/w16233502